Inovasi Pelayanan Kesehatan Publik Berbasis e-Government (Studi Kasus: Inovasi Ayo Ceting di Puskesmas Andalas) - Iip Permana; Ulfia Izzati (Faculty of Social Science, Universitas Negeri Padang, 2020)
Health is a fundamental thing in human life. Healthy development is an investment for the development of Indonesian communities, therefore increasing community awareness, willingness, and abilities is a must. Benchmarking of success in health development is the creation of quality public health services. Increasing challenges in health development, impacting on public health services become less optimal. The government tries to improve the quality of public health services by creating various innovations through digital technology. Andalas Community Health Center as part of the government improves the quality of health services through Ayo Ceting Program, which aims to prevent stunting in the District of East Padang. Ayo Ceting consists of three program packages namely, WhatsApp Group for Pregnant Mothers, Rumah Gizi and Digital Education: The Ayo Ceting Android-based application. This study aims to determine the implementation of Ayo Ceting innovation at Andalas Public Health Center, Padang City. This research uses a qualitative descriptive approach, where research is conducted to obtain and collect in-depth data directly from the research location regarding the use of Ayo Ceting applications. The informants in this study were health workers responsible for the stunting prevention innovation program at the Andalas Public Health Center in Padang. Based on the explanation from sources, Ayo Ceting innovation increasing people's knowledge and understanding of Stunting and it prevention and empowering the community itself to actively report their health data. Furthermore, it provides more effective and efficient public services, and finally, the community can obtain information with access and a more attractive appearance